In-Vitro Antileishmanial Activity of Raphanus sativus L. var. caudatus - Ishrat Younus; Afshan Siddiq (Journal of Basic & Applied Sciences, 2016)
Leishmaniasis is a major public health problem causing significant morbidity and mortality around the world specially Asia, Africa and Latin America. The present preliminary in-vitro study reports antileishmanial potential of Raphanus sativus L. var. caudatus. Various concentrations of ethanolic extract of plant were used. The tested extract showed noteworthy inhibition (concentration – dependant) of Leishmania promastigotes. The IC50 of extract was found to be 39 μg/ml. The results of present study could be helpful in future for antileishmanial therapy.